Minimal access rectal cancer surgery: an observational study of patient outcomes from a district general hospital with over a decade of experience with robotic rectal cancer surgery. (18th July 2021) - Tilney, Henry S.; Huddy, Jeremy R.; Nizar, A. Shiyam; Smith, Ralph; Gudgeon, A. Mark
Abstract: Aim: Robotic surgery for colorectal cancer has become established more slowly than in other specialities. The aim of this study was to assess the risks and benefits of the use of robotic rectal cancer surgery in comparison with laparoscopic surgery within the confines of a subspecialist rectal cancer service in a district general hospital. Method: Outcomes from consecutive patients undergoing minimal access rectal cancer surgery between July 2008 and January 2020 were analysed. Comparisons were made between short‐term outcomes including conversion rates, anastomotic leakage and pathological outcomes as well as long‐term survival and cancer recurrence. Results: A total of 337 patients were included in the analysis, 204 (60.5%) of whom underwent robotic surgery. Demographic characteristics and use of neoadjuvant chemoradiotherapy were similar between groups. However, patients having robotic surgery had significantly lower tumours than in the laparoscopic group (7.6 cm vs. 9.8 cm, p  = 0.003). Conversion to open surgery in the robotic group was significantly less likely (9.8% vs. 22.6%, p  = 0.001). Operative mortality, clinical leakage and major complications were similar between groups. While asymptomatic 'radiological' leaks were significantly more common following robotic surgery (13.7% vs. 5.3%, p  = 0.017) this did not affect the long‐term stoma closure rate. Pathological outcomes were similar with the exception of shorter mean distal resection margins (25.9 mm vs. 32.8 mm, p  = 0.001) for the robotic group of patients. There was no statistical difference in 5‐year survival between groups (78.7% robotic vs. 85.4% laparoscopic, p  = 0.263) nor local recurrence (2.0% robotic vs. 3.8% laparoscopic, p  = 0.253). Conclusions: These results illustrate how the selective use of robotic surgery by a dedicated rectal cancer team can achieve low rates of cancer recurrence and low permanent stoma rates.